Glucocorticoid toxicity index - Kaymaz Tahra, Sema; Bahap Kara, Melda (Acta Medica, 2024)
The Glucocorticoid Toxicity Index (GTI) is a glucocorticoid-related toxicity measurement tool which was recently developed by an international expert panel. GTI can be calculated with two different methods: Cumulative Worsening Score (CWS) and Aggregate Improvement Score (AIS). The total glucocorticoid-related toxicity during follow-up can be calculated with CWS. All parameters that develop over time continue to be included, and a decrease in the CWS is not possible. On the contrary, both increase and decrease in toxicity can be assessed in scoring with the AIS method. A drug that reduces glucocorticoid toxicity should be able to reduce the AIS score. Cumulative glucocorticoid dose was found to be associated with higher GTI scores in studies. Although not all glucocorticoid-related toxicities can be covered, parameters that are common, dynamic, and more likely to be glucocorticoid-related are included in GTI. GTI has some limitations such as the possibility of not detecting chronic damage, the difficulty in interpreting the score in the patients who have already sterted the glucocorticoid treatment, some parameters requiring direct interaction with the patient, and difficulty in calculation.